Prevalence of stress, depression, anxiety and sleep disturbance among nurses during the COVID-19 pandemic: A systematic review and meta-analysis - Al Maqbali, Mohammed; Al Sinani, Mohammed; Al-Lenjawi, Badriya (Journal of psychosomatic research, 2021)
The new coronavirus disease's (COVID-19) high risk of infection can increase the workload of healthcare workers, especially nurses, as they are most of the healthcare workforce. These problems can lead to psychological problems. Therefore, the aim of this systematic review and meta-analysis to ascertain the present impact of the COVID-19 outbreak on the prevalence of stress, anxiety, depression and sleep disturbance among nurses. A systematic review and meta-analysis were conducted. The following databases were searched: PubMed, CHINAL, MEDLINE, EMBASE, PsycINFO, MedRxiv and Google Scholar, from January 2020 up to 26th October 2020. Prevalence rates were pooled with meta-analysis using a random-effects model. Heterogeneity was tested using I-squared (I2) statistics. A total of 93 studies (n = 93,112), published between January 2020 and September 2020, met the inclusion criteria. The overall prevalence of stress was assessed in 40 studies which accounted for 43% (95% CI 37–49). The pooled prevalence of anxiety was 37% (95% CI 32–41) in 73 studies. Depression was assessed in 62 studies, with a pooled prevalence of 35% (95% CI 31–39). Finally, 18 studies assessed sleep disturbance and the pooled prevalence was 43% (95% CI 36–50). This meta-analysis found that approximately one third of nurses working during the COVID-19 epidemic were suffering from psychological symptoms. This highlights the importance of providing comprehensive support strategies to reduce the psychological impact of the COVID-19 outbreak among nurses under pandemic conditions. Further longitudinal study is needed to distinguish of psychological symptoms during and after the infectious disease outbreaks. •Meta-Analysis was conducted included 93 studies of 93,112 nurses.•Prevalence of depression and anxiety were 35% and 37% among nurses.•Prevalence of stress and sleep disturbance were 43% and 43% among nurses.•A strategy to reduce psychological impact of COVID-19 among nurses is required.